(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study was to find out how the accountability of the Provincial Legislatives Council (DPRD) in supervising local regulations regarding the Sungguminasa traditional market in Gowa Regency. This study used a qualitative research method. Data was collected by interviews, documentation, observation. Legitimacy was the acceptance of a decision by a leader that according to the procedure that applied to society. Legitimacy was related to legal issues and the application of laws. It could be used as a measure of how the decision could be accepted and its validity recognized by the community. The results of this study showed that DPRD supervision of traditional market was still not good enough with market conditions. It was still muddy and several abandoned stalls, no sanctions for swords selling on the side of the road and irregular parking arrangements.